Living waste: making a life in wasted spaces - Kutlu, Yusuf. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This thesis traces a case of how internally displaced Kurds make a life after being forced to migrate to the cities of western Turkey. The research was conducted with internally displaced Kurdish waste pickers living in the Tarlabaşı district of İstanbul and takes their working processes, their life practices, politics, intellectuality and aesthetics as a significant research framework. Since the aim is the making of a life in the informal space of Tarlabaşı, I examine how they produce space, time, and practices through their labor process, political practices, writings and intellectual, artistic and aesthetic products. My thesis argument is that the informal space of Tarlabaşı provides opportunities for internally displaced Kurds to make a life outside of modern state grounds, i.e. in a space of autonomy. Existing in this autonomous space produces practices of transgressing state power permanently for the purpose of making a life, despite intentionally emerged political aims and agendas that target state power. In so doing, life itself consists of perpetual practices of violating not only state power (by illegally obtaining its amenities), but also capitalist market relationships, modern urban life’s established normativity, and notions of regulated time and space in the city. Furthermore, I show how waste pickers apprehend and sense the world, and distinguish the common, structured and hegemonic way of the sensible. It is an attempt to find how internally displaced Kurdish waste pickers escape from the formal, the constituted, the normative and create a new way of living and being in the informal space.
Keywords: Kurds -- Turkey.; Kurds -- Turkey -- Ethnic identity.